«Гранична ситуація» (К.Ясперс) як категорія екзистенційної соціології - Мельніков, Андрій Сергійович; Мельніков, А. С.; Мельников, Андрей Сергеевич; Melnikov, Andrii S. (Чернівці : Чернівецький нац. ун-т, 2013)
У статті стверджується необхідність розвитку екзистенціальної соціології як найбільш адекватного підходу до дослідження сучасної соціальної реальності. У зв'язку з цим аналізуються ідеї німецького філософа К. Ясперса про прикордонній ситуації та ставиться питання про затребуваність включення відповідної категорії в структуру екзистенціальної соціології. На закінчення намічаються загальні перспективи подальших соціологічних досліджень граничних ситуацій.

В статье утверждается необходимость развития экзистенциальной социологии как наиболее адекватного подхода к исследованию современной социальной реальности. В связи с этим анализируются идеи немецкого философа К. Ясперса о пограничной ситуации и ставится вопрос о востребованности включения соответствующей категории в структуру экзистенциальной социологии. В заключение намечаются общие перспективы дальнейших социологических исследований граничных ситуаций.

The paper states the need to develop existential sociology as the most appropriate approach to the study of contemporary social reality. In connection with this position, the ideas of German philosopher Karl Jaspers on “limit situation” are analyzed. The analysis concerns typology of situations (general, historical, and limit situations), definition of limit situation, and it main forms – death, suffering, struggle, and guilt. Author asserts the inclusion of category “limit situation” to the structure of existential sociology on several levels, such as general sociological theory (conception) of limit situations, micro and macro approaches to limit situations, middle range theories of limit situations (sociology of emotions, sociology of suffering, sociology of disasters, sociology of religion, sociology of war, etc.). Generally, prospects of further sociological studies of limit situations are proposed.
Мельніков А. «Гранична ситуація» (К.Ясперс) як категорія екзистенційної соціології / А. Мельніков // Релігія та Соціум. Міжнародний часопис. – Чернівці: Чернівецький нац. ун-т, 2013. – № 1 (9). – С. 66-71.
Keywords: гранична ситуація; екзистенціальна соціологія; філософія К. Ясперса; негативний досвід; зміна свідомості; граничная ситуация; экзистенциальная социология; философия К. Ясперса; негативный опыт; изменение сознания; limit situation; existential sociology; philosophy of Karl Jaspers; negative experience; change of consciousness; Research Subject Categories::SOCIAL SCIENCES